Efektivitas Pelaksanaan Fatwa DSN-MUI Tentang Sanksi Nasabah Pembiayaan Bermasalah Pada Produk BSI OTO - Dewi, Miftah Rosiana; Fakhrina, Agus; Qiptiyah, Mariatul (el hisbah Journal of Islamic Economic Law, 2024)
This study aims to analyze the effectiveness of the implementation of DSN-MUI Fatwa No. 17/DSN-MUI/IX/2000 concerning sanctions for capable customers who delay payments on BSI OTO financing at BSI Kajen Pekalongan. And analyze the factors that influence its effectiveness. This research method uses empirical juridical with a case study approach and legislation. The resulting data are analyzed using descriptive analysis techniques. The results of the study indicate that the late payment fine policy for financing, implemented by BSI Kajen Pekalongan on BSI OTO products, has proven effective in improving customer discipline and managing financing risks. The fine is only imposed on customers who are capable but deliberately delay (mumatil) payment of financing installments. The fine may be imposed as a form of ta'zīr (social/financial punishment). The main factors that support this effectiveness include strict compliance with sharia principles, where fine funds are not a source of bank income, but are allocated for social and charitable activities. This research contributes to the development of Islamic economic law studies and the evaluation of the application of the DSN-MUI Fatwa on financing products in Islamic Financial Institutions.